Performance of Steel Fiber-Reinforced Concrete Pier under Impact Load - Melaknesh Dessalegn; Temesgen Wondimu (Advances in Civil Engineering, 2022)
Vehicular impact on bridge piers is one of the leading causes of bridge failure. Due to the increase in vehicle-pier collisions, many researchers have studied the performance of RC bridge piers under vehicle collisions. Adding steel fiber is an alternative way to improve the impact resistance of concrete structures and enhance their capacity for energy absorption. However, a study on the performance of piers with steel fiber-reinforced concrete under impact load is limited. This study examines the performance of steel fiber-reinforced concrete (SFRC) bridge piers subjected to impact loading. To study the impact behavior of SFRC piers, a numerical model of bridge piers with impact mass was developed by LS-DYNA. The reliability of the numerical analysis was validated. To investigate the effects of impact mass, impact velocity, the volume of steel fiber, concrete grade, and percentage of longitudinal reinforcement on the impact behaviors of piers and the impact forces, parametric studies were carried out. The finite element analysis revealed that the addition of steel fiber resists lateral deformation and significantly affected the failure modes of bridge piers under impact loading. Moreover, the deformation of the impacted piers and the impact force is mainly affected by the addition of steel fiber, impact energy, and percentage of longitudinal reinforcement and is not sensitive to concrete strength.